(untitled) (Tikrit Journal For Political Science, 2025)
The qualifications possessed by the United States of America in the field of cybersecurity are an important foundation upon which the American decision-maker relies in achieving the goals of the National Security Strategy according to the strategic perception, in a way that made the United States of America work to manage this force within a purposeful framework that seeks to use the resources of some countries of the world to its advantage and to formulate partnerships with some other countries by adopting the approach of containment, dismantling, and reassembly in a way that suits and achieves American objectives, as artificial intelligence is one of the foundations of cybersecurity that has been employed. In electronic warfare, it made a big difference in curbing the capabilities of the opponent, and this is what the American administration seeks to achieve to achieve its ambition for global hegemony and control.